2013
DOI: 10.1177/0142723713503145
|View full text |Cite
|
Sign up to set email alerts
|

An examination of language input and vocabulary development of young Latino dual language learners living in poverty

Abstract: The purpose of the study was to evaluate the language status of 120 young, Latino dual language learners living in poverty in the United States. Maternal language input and home language and literacy environments were examined with regard to language development at 24 and 36 months. Results suggested that even when combining English and Spanish language knowledge scores, the children in this sample still performed below, albeit closer to, age level. The home language and literacy environments were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 53 publications
(71 reference statements)
4
30
1
Order By: Relevance
“…As mentioned, previous studies have reported direct relations between linguistic input and children’s language-specific vocabulary size (for Spanish-English bilinguals); additionally, studies have reported relations between cultural factors, specifically acculturation, and bilingual children’s language development. For example, Boyce, Gillam, Innocenti, Cook, and Ortiz (2013) found that maternal factors (including maternal acculturation) and the home language/literacy environment each predicted Spanish-English bilingual children’s total vocabulary size at 24 months (see also Hammer, Miccio, & Rodriguez, 2004). However instead of exploring direct relations between mothers’ acculturation and children’s language learning as previous researchers have done, we hypothesized that mothers’ acculturation level would influence their childrearing decisions with respect to the language environment that they create for their children (input), which in turn would influence children’s language development.…”
Section: Determinants Of Inputmentioning
confidence: 99%
“…As mentioned, previous studies have reported direct relations between linguistic input and children’s language-specific vocabulary size (for Spanish-English bilinguals); additionally, studies have reported relations between cultural factors, specifically acculturation, and bilingual children’s language development. For example, Boyce, Gillam, Innocenti, Cook, and Ortiz (2013) found that maternal factors (including maternal acculturation) and the home language/literacy environment each predicted Spanish-English bilingual children’s total vocabulary size at 24 months (see also Hammer, Miccio, & Rodriguez, 2004). However instead of exploring direct relations between mothers’ acculturation and children’s language learning as previous researchers have done, we hypothesized that mothers’ acculturation level would influence their childrearing decisions with respect to the language environment that they create for their children (input), which in turn would influence children’s language development.…”
Section: Determinants Of Inputmentioning
confidence: 99%
“…The impact of SES on caregivers', as well as children's, language is far reaching. Hart and Risley (1995) and many subsequent studies showed that children with a lowSES background hear significantly fewer words than their more affluent peers, and this gap has a cascade of consequences: smaller vocabularies (Boyce, Gillam, Innocenti, Cook, & Ortiz, 2013;Wu & Gros-Louis, 2014), lower intelligence scores, poorer academic success (Nelson, Welsh, Trup, & Greenberg, 2011), etc. Moreover, the dramatic consequences of SES differences are indicated from early on in life.…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of poverty on brain development, language acquisition, and reading comprehension have been well documented (Boyce et al, 2013;Kolb & Gibb, 2016; Vernon-Feagans, Garrett-Peters, Willoughby & Mills-Koonce, 2012).…”
Section: Students In Povertymentioning
confidence: 99%